1984
DOI: 10.1136/jnnp.47.11.1182
|View full text |Cite
|
Sign up to set email alerts
|

Studies on regional cerebral oxygen utilisation and cognitive function in multiple sclerosis.

Abstract: SUMMARY Regional cerebral oxygen utilisation (rCMRO2), oxygen extraction (rOER), blood flow (rCBF), and blood volume (rCBV) have been determined for fifteen patients with multiple sclerosis in remission using positron emission tomography (PET). Cerebral oxygen utilisation and blood flow were significantly reduced in both white matter and peripheral cortical grey matter in the multiple sclerosis patients compared to a group of normal controls. No evidence of regional cerebral ischaemia in the multiple sclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
59
0
3

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(74 citation statements)
references
References 20 publications
(3 reference statements)
12
59
0
3
Order By: Relevance
“…This is in line with the findings of previous studies using PET and singlephoton emission computed tomography (Blinkenberg et al, 2000;Brooks et al, 1984;Lycke et al, 1993;Paulesu et al, 1996;Pozzilli et al, 1991;Roelcke et al, 1997), which have demonstrated a generalized coupled reduction in both cerebral oxygen utilization and blood flow in patients with established MS. Hypoperfusion was reported in both WM and GM and correlated with cognitive impairment rather than with locomotor disability, thus reiterating that the EDSS is heavily weighted toward locomotor disability and that the cerebral functional system is of limited sensitivity. Most PET and single-photon emission computed tomography studies, however, investigated only patients affected by RR-MS and, with very few exceptions (Paulesu et al, 1996;Pozzilli et al, 1991), cognition was assessed using the mini mental status scale or the cerebral functional system of the EDSS.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the findings of previous studies using PET and singlephoton emission computed tomography (Blinkenberg et al, 2000;Brooks et al, 1984;Lycke et al, 1993;Paulesu et al, 1996;Pozzilli et al, 1991;Roelcke et al, 1997), which have demonstrated a generalized coupled reduction in both cerebral oxygen utilization and blood flow in patients with established MS. Hypoperfusion was reported in both WM and GM and correlated with cognitive impairment rather than with locomotor disability, thus reiterating that the EDSS is heavily weighted toward locomotor disability and that the cerebral functional system is of limited sensitivity. Most PET and single-photon emission computed tomography studies, however, investigated only patients affected by RR-MS and, with very few exceptions (Paulesu et al, 1996;Pozzilli et al, 1991), cognition was assessed using the mini mental status scale or the cerebral functional system of the EDSS.…”
Section: Discussionsupporting
confidence: 92%
“…23 However, an SWI study at 3T demonstrated a significantly reduced visibility of the venous vasculature in the periventricular white matter (WM) of patients with RRMS. 24 In line with previous positron-emission tomography studies, which showed a reduction of oxygen use and extensive hypometabolism in the GM and normal-appearing (NA) WM of patients with MS, 25,26 this reduced visibility and volume of the cerebral venous system, reflecting a decreased venous blood deoxyhemoglobin concentration, can be interpreted as a result of a decreased oxygen extraction in the diseased MS tissue. On the contrary, occlusion of the venous vasculature should lead to an intracranial venous engorgement (increased visibility and volume) and enhancement of susceptibility effects, due to increased oxygen extraction.…”
Section: Neuroimaging Studies Directly Assessing the Ccsvi Theorysupporting
confidence: 80%
“…This finding is consistent with positron emission tomography studies that found no regional distribution to metabolic abnormalities in MS, and posited that cerebral metabolic hypoactivity in the disease may reflect autoimmune changes in the brain independent of focal, visible lesions. 5,13 These diffuse OEF changes may also explain the excellent intraobserver (COV = 2.1%), interobserver (COV = 5.2%), and scan-rescan (COV = 5.9%) agreement of mean cortical OEF values in controls and patients, even though vessels were selected independently for all reproducibility analyses.…”
Section: Discussionmentioning
confidence: 97%
“…Initial studies on brain oxygen consumption in MS performed using 15 O positron emission tomography showed reductions of absolute cerebral blood flow and cerebral oxygen metabolism in both gray matter (GM) and white matter (WM). 5,13 Similarly, MRI observations of decreased T 2 * relaxation rate in frontal normal-appearing WM 14 and reduced visibility of periventricular veins on susceptibility-weighted images 15 indicate decreased oxygen extraction in MS. T 2 *-weighted imaging at 7 T has also revealed vascular alterations (reduced periventricular venous density) in patients that are consistent with widespread hemodynamic and metabolic changes related to the disease. 16 In a previous study, Ge et al 17 applied T2-relaxation-under-spin-tagging MRI to directly measure absolute OEF in the sagittal sinus of patients with relapsing-remitting MS (RRMS) with MRI.…”
Section: Introductionmentioning
confidence: 98%